Development of Novel Cloud-Based Clinical Credentialing and Training Checklist System to Improve Volunteer On-Boarding and Certification Tracking in a Student-Run Free Clinic - Nott, Rohini; Patel, Nina; Hartmark-Hill, Jennifer (Journal of Student-Run Clinics, 2019)
Interprofessional, student-run free clinics oversee many volunteers of different disciplines who may participate in multiple outreach programs. Effective organizational volunteer management is crucial to achievement of mission goals and volunteer retention. Students from different organizational and educational backgrounds may be required to complete a number of unique certifications and trainings in order to volunteer in a clinical role. Clear and concise dissemination of requirements to both new and returning volunteers must be performed in a structured and replicable way to ensure organizational consistency and accuracy. The Student Health Outreach for Wellness (SHOW) Community Initiative serves vulnerable populations in a variety of clinical settings, including outreaches to people experiencing homelessness and those in treatment for substance abuse disorders. Implementation of the cloud-based clinical checklist and volunteer roster has enabled our student-run free clinic to more effectively communicate both within our volunteer management team and with clinical volunteers we oversee. This article describes how a novel volunteer management workflow strategy was employed to improve volunteer compliance and communication between clinical staff and volunteers and volunteer onboarding efficiency, as well as how other student-run free clinics can implement similar strategic workflow practices to optimize their volunteer management efficiency and efficacy.